A functional high‐content miRNA screen identifies miR‐30 family to boost recombinant protein production in CHO cells. Issue 10 (26th August 2014) - Fischer, Simon; Buck, Theresa; Wagner, Andreas; Ehrhart, Carolin; Giancaterino, Julia; Mang, Samuel; Schad, Matthias; Mathias, Sven; Aschrafi, Armaz; Handrick, René; Otte, Kerstin
Abstract The steady improvement of mammalian cell factories for the production of biopharmaceuticals is a key challenge for the biotechnology community. Recently, small regulatory microRNAs (miRNAs) were identified as novel targets for optimizing Chinese hamster ovary (CHO) production cells as they do not add any translational burden to the cell while being capable of regulating entire physiological pathways. The aim of the present study was to elucidate miRNA function in a recombinant CHO‐SEAP cell line by means of a genome‐wide high‐content miRNA screen. This screen revealed that out of the 1, 139 miRNAs examined, 21% of the miRNAs enhanced cell‐specific SEAP productivity mainly resulting in elevated volumetric yields, while cell proliferation was accelerated by 5% of the miRNAs. Conversely, cell death was diminished by 13% (apoptosis) or 4% (necrosis) of all transfected miRNAs. Besides these large number of identified target miRNAs, the outcome of our studies suggest that the entire miR‐30 family substantially improves bioprocess performance of CHO cells. Stable miR‐30 over expressing cells outperformed parental cells by increasing SEAP productivity or maximum cell density of approximately twofold. Our results highlight the application of miRNAs as powerful tools for CHO cell engineering, identified the miR‐30 family as a critical component of cell proliferation, and support the notion that miRNAs are powerful determinants of cell viability.